Hot Electrons and Hot Spins at Metal–Organic Interfaces. (20th December 2017) - Arnold, Thorsten; Atxabal, Ainhoa; Parui, Subir; Hueso, Luis E.; Ortmann, Frank
Abstract: A model is developed to describe the electron transport properties of hot electron devices based on organic semiconductors. For the first time, the simulations cover all the different processes the carriers experience in the device, which allows disentangling various effects on the transport characteristics. The model is compared to experimental measurements and excellent agreement is found. In addition, the model includes the electron spin and is thus able to describe a hot spin transistor. In this device, a spatial variation of the spin diffusion length is found, which scales inversely proportional to the variation of the electron density. The spin current can be increased by increasing the hot electron energy and by decreasing the image charge barrier without changing the spin diffusion length. Unprecedented insight into the effect of interfacial disorder at the metal–organic interface on charge and spin transport is provided. Finally, conditions are established, where majority and minority spin carriers propagate in opposite directions, increasing the spin current relative to the charge current and the occurrence of pure spin currents is analyzed. Abstract : An electron transport model for hot electron devices based on organic semiconductors is developed. It covers hot electron generation, inelastic scattering, electron injection, and hopping in multiple transport levels. The model is capable to describe the experimental current–voltage characteristics. It is further extended to spin transport. Under certain conditions, pure spin currents are observed.